1997
DOI: 10.1002/(sici)1097-4628(19970516)64:7<1411::aid-app21>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glycerol and water content on the structure and properties of extruded starch plastic sheets during aging

Abstract: ABSTRACT:The properties of starch plastic sheets were investigated by stress-strain measurements in relation with starch crystallinity. Granular potato starch was plasticized with different amounts of glycerol and water by extrusion. The materials were amorphous directly after processing. During aging above the glass transition temperature at various humidities single helical (V and E-type) and double helical (B-type) crystallinity was formed. The rate of crystallization is a function of water and glycerol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(138 citation statements)
references
References 8 publications
9
115
1
1
Order By: Relevance
“…A simple and common technique of producing sheet or film by extrusion is using a twin-screw extruder with a slit or flat film die followed by a take-off device for orientation and collection (van Soest and Knooren 1997;Fishman, Coffin et al 2000;Yu and Christie 2004;Dean, Yu et al 2007). During film or sheet extrusion, the viscoelastic starch-based materials are forced through the die to form sheet or film products (Chiang and Johnson 1977).…”
Section: Introductionmentioning
confidence: 99%
“…A simple and common technique of producing sheet or film by extrusion is using a twin-screw extruder with a slit or flat film die followed by a take-off device for orientation and collection (van Soest and Knooren 1997;Fishman, Coffin et al 2000;Yu and Christie 2004;Dean, Yu et al 2007). During film or sheet extrusion, the viscoelastic starch-based materials are forced through the die to form sheet or film products (Chiang and Johnson 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (1998) hold that TP maize starch with 10% moisture and 25-35% glycerol shows a T g running from 83 -71°C. Van Soest & Knooren (1997) proved that potato TPS with 11% moisture and 26% glycerol had a T g = 40 °C, whereas for the materials of higher moisture and glycerol content it fell below 20°C. Lourdin et al (1997) reported that potato starch of 13% moisture with 15% glycerol content had the T g around 25°C, while at 25% glycerol the T g dropped to around 0°C.…”
Section: Thermoplastic Starchmentioning
confidence: 96%
“…If the total thermal and mechanical energy provided to the starch is insufficient the product will show unmolten starch granules of clear crystallographic structure. Similarly, an insufficient amount of plasticizer may result in incomplete destruction of the crystallographic structure of starch (Souza & Andrade, 2002;Van Soest & Knooren, 1997). …”
Section: Thermoplastic Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of starch to obtain films is attributed to chemical, physical and functional properties of amylose. The amylose molecules in solution are arranged in parallel, forming hydrogen bonds among adjacent starch chains, reducing polymer water affinity and favoring the obtainment of opaque gels and reduced flexibility films (Lu, 2009;Shimazu, 2007;Jansson, Thuvander, 2004;Soest, Knooren, 1997). The mechanical properties of starch films can be changed by addition of plasticizing agents.…”
Section: Introductionmentioning
confidence: 99%